A Digital Learning Approach to Improve Students Vocabulary in Language Teaching: Utilizing Google Sites - Qurrata'ain, Qurrata'ain; Putra, Ida Nyoman Tri Darma; Evalinda, Greis; Arif, Muhammad (Journal of Linguistics and Social Studies, 2025)
The digital transformation era has revolutionized education, emphasizing the need for innovative teaching methods. This study explores the integration of Google Sites as a platform for delivering vocabulary course instructions to address challenges such as demotivation, inefficiency, and lack of accessibility in traditional methods. Conducted with 36 undergraduate students from teaching training and education faculty at Nusa Cendana University, the research employed pre-test and post-test evaluations to measure the impact of the platform. Key features of the developed Google Site include multimedia elements, interactive quizzes, and collaborative tasks tailored to enhance engagement and learning outcomes. Results indicate a significant improvement in students' vocabulary proficiency, as evidenced by a statistically significant difference in pre-test and post-test scores (t=-9.6152, p less than 0.05. A large absolute value signals a very strong effect. The findings highlight the potential of Google Sites to transform vocabulary instruction by fostering motivation, accessibility, and effective learning.